Ultrasonication for the Control of Aphelenchoides besseyi in Local Rice Seed Varieties from North Sumatra - Della Sitanggang; Supramana Supramana; Tri Asmira Damayanti (Jurnal Perlindungan Tanaman Indonesia, 2026)
Aphelenchoides besseyi is one of the most important plant parasitic nematode in rice causing the white tip disease. Its dormant phase is seed-borne, making rice seeds a medium for the long-distance dispersal of this nematode. This study aimed to assess the potential of ultrasonic wave application as a seed treatment method for eliminating A. besseyi nematodes from rice seeds. The seed varieties tested were six local varieties from North Sumatra namely Siserang, Sipining, Sipala, Sirias, Sigambiri Merah, and Sigambiri Putih. The commercial rice variety Pak Tiwi-1 was used as a comparison. Seed treatment was conducted with an ultrasonic cleaner unit at 40 kHz for 5, 10, 15, 20, 25, and 30 minutes, respectively.  Ultrasonic exposure at 40 kHz for 20 and 30 minutes were able to eliminate A. besseyi by 100%, resulting in 0% incidence of white tip disease in seedlings. Ultrasonic seed treatment shows potential as an effective, practical, and relatively fast technique for eliminating A. besseyi from rice seeds.